Structural band-gap tuning in g-C3N4. Issue 2 (19th November 2014) - Zuluaga, Sebastian; Liu, Li-Hong; Shafiq, Natis; Rupich, Sara M.; Veyan, Jean-François; Chabal, Yves J.; Thonhauser, Timo
Abstract : Experimental and theoretical results uncover an almost perfectly linear relationship between the band gap and structural aspects of g-C3 N4, allowing the tuning of the frequency at which g-C3 N4 absorbs light. Abstract : g-C3 N4 is a promising material for hydrogen production from water via photo-catalysis, if we can tune its band gap to desirable levels. Using a combined experimental and ab initio approach, we uncover an almost perfectly linear relationship between the band gap and structural aspects of g-C3 N4, which we show to originate in a changing overlap of wave functions associated with the lattice constants. This changing overlap, in turn, causes the unoccupied p z states to experience a significantly larger energy shift than any other occupied state (s, p x, or p y ), resulting in this peculiar relationship. Our results explain and demonstrate the possibility to tune the band gap by structural means, and thus the frequency at which g-C3 N4 absorbs light.